2012
DOI: 10.1038/bmt.2012.116
|View full text |Cite
|
Sign up to set email alerts
|

Tandem autologous-allo-SCT is feasible in patients with high-risk relapsed non-Hodgkin’s lymphoma

Abstract: Allo-SCT is used to exploit GVL effect in high-risk relapsed non-Hodgkin's lymphoma (NHL). Here, we retrospectively analyzed 34 high-risk NHL patients who underwent auto-SCT followed closely by reduced-intensity allo-SCT ('tandem auto-allo') from January 2002 to November 2010. The search for an allogeneic donor was started at the beginning of salvage regimen. Median patients' age was 47 (27-68) years; histotypes were: diffuse large B-cell n ¼ 5, follicular n ¼ 14, transformed follicular n ¼ 4, mantle-cell n ¼ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…12,[24][25][26] In the setting of double HDC, a prospective study from the former GELA/SFGM group showed that, in the higher-risk group of patients (refractory and with more than two adverse prognostic factors), this approach of the 5-year freedom from second failure and OS was 41% and 52%, respectively, with the better results in those with chemosensitive disease to salvage therapy. 27 In a pilot study adopting the double HDC approach, Fung et al 28 reported that, in refractory or poor-prognosis patients, the 5-year OS, PFS and freedom from progression were 54%, 49% and 55%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,[24][25][26] In the setting of double HDC, a prospective study from the former GELA/SFGM group showed that, in the higher-risk group of patients (refractory and with more than two adverse prognostic factors), this approach of the 5-year freedom from second failure and OS was 41% and 52%, respectively, with the better results in those with chemosensitive disease to salvage therapy. 27 In a pilot study adopting the double HDC approach, Fung et al 28 reported that, in refractory or poor-prognosis patients, the 5-year OS, PFS and freedom from progression were 54%, 49% and 55%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] However, prognosis of HL patients who do not undergo transplantation remains poor; indeed, the importance of an effective salvage therapy mainly resides in the ability to bridge refractory patients to auto-or even allo-SCT when in response of their disease. 11,12 Our group previously reported an overall response rate (ORR) of 81% after high-dose melphalan (HD-PAM), followed by autologous stem cell infusion in 42 lymphoma patients; in that study the response to treatment was evaluated by computed tomography. 13 Those encouraging findings allowed us to continue using the same regimen even after the advent of FDG-PET for the evaluation of response.…”
Section: Introductionmentioning
confidence: 99%
“…Marseille and Milan groups reported the results of 34 high-risk relapsed NHL patients, including 14 patients with FL, who underwent tandem BEAM or high-dose Mel auto-SCT followed by RIC (Flu + Bu + ATG or Flu + Cy with or without thiotepa) allo-SCT. 58 The 5-year OS and PFS were 77% and 68%, respectively, with a 2-year TRM of 6%. The clinical implications of preceding auto-SCT before RIC allo-SCT should be confirmed by further large-scale studies.…”
Section: Novel Conditioning Regimensmentioning
confidence: 99%
“…Introduction of reduced intensity conditioning (RIC) regimens lowered NRM in HL and other diseases, allowing allo-HCT to be offered to a higher proportion of heavily pretreated cases. [48][49][50][51] Myeloablative regimens A NRM exceeding 50% was reported after myeloablative allo-HCT for relapsed HL. [52][53][54] Although many factors influence outcome, such as high number of prior therapies, hence late referrals for allografting, and suboptimal performance status, another reason for such a high mortality rate could be partly attributed to using myeloablative regimens in patients with comorbidities.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%